GUIDELINES IN CLINICAL PRACTICE: A DICTUM OR A DAMN..?! - TP, Rajeev; Krishnan, Shalini (Journal of Health and Allied Sciences NU, 2015)
Clinical practice guidelines are systematically developed statements that assist practitioners to provide appropriate evidence-based care. They are often created by statutory bodies, expert associational advisory committees, government and regional offices and even individual hospital policy groups. The objectives of clinical guidelines are to standardize medical care, to raise the quality of care and to reduce several kinds of risks to the patient and health care provider. Implementation of clinical practice guidelines is a complex process and protocols with good quality, with clinical importance and prioritization of topics, and a user-friendly format are usually successful. In day to day clinical practice guidelines are not strictly followed. The merits and demerits of guideline based practice patterns have been analyzed here. There could be many reasons for the non adherence to protocol based medical practice which has to be addressed. A historical perspective of guidelines and a breach in standardized practice is also mentioned. As there can be fallacies in protocols; a clinical practice that is not strictly adhering with guidelines, should not be considered as a wrongful treatment strategy.
Keywords: Guidelines; protocol; clinical practice; adherence